Environmentally Friendly Behavior of Islamic Bank Employees: The Role of Islamic Banks in Maintaining Sustainability - Adhitya, Fajar; Farida, Dessy Noor; Singh, Malika (Economica: Jurnal Ekonomi Islam, 2024)
The challenges of climate change and the recent energy crisis have increased the importance of environmental sustainability, with green technology emerging as a key driver of sustainable growth. In response, Sharia-compliant banking has integrated green banking principles to promote environmental protection. This study examines the green behaviors of Islamic bank employees and their impact on the growth of green banking. Focusing on Islamic banks in Central Java, Indonesia, a sample of 100 employees was selected through purposive probability sampling. Data were collected using questionnaires, and multiple linear regression analysis was conducted using IBM SPSS to assess the relationships between variables. The findings reveal that behaviors such as conserving resources, working sustainably, avoiding harm, taking initiative, and influencing others significantly contribute to green banking growth. The results suggest that encouraging green behavior among bank employees plays a vital role in expanding green banking practices within Islamic banks, aligning the sector with sustainable development goals through environmentally responsible actions. However, the study is limited by the relatively small sample size of 100 respondents, which may affect the generalizability of the findings. Future research should consider a larger sample size to validate the results and provide broader insights into the role of employee behavior in green banking.